Authority and Ulama In Aceh: The Role of Dayah Ulama In Contemporary Aceh Religious Practices - Syafieh, Syafieh; Muhaini, Muhaini; Syufyan, Suhaili (The Faculty of Islamic Theology and Humanities, UIN Walisongo Semarang, Indonesia, 2022)
Recently, the traditionalist ulama dayah has been questioned in Aceh. With the arrival of religious groups with a Wahhabi-Salafi pattern, Acehnese dayah ulama have lost their authority as agents or religious figures in Acehnese society. This study focuses on the authority of the dayah ulama and its role in contemporary Acehnese spiritual practice. This study aims to see the authority of the dayah ulama amid the development of Wahhabi-Salafi understanding in contemporary Aceh. By conducting interviews with the dayah ulama group, Wahhabi-Salafi groups, and related government institutions in the province of Aceh and using qualitative data analysis, the researcher found that the role of the dayah ulama was still strong in influencing the religious practice of contemporary Acehnese society as evidenced by the community's rejection of Salafist religious understanding. Fundamentalism developed in Aceh because it was not by understanding the dayah ulama, namely the doctrine of Ahlusunnah Waljamaah. In addition, there is support from the Aceh government for the religion of the dayah ulama, with evidence by the issuance of a circular regarding the obligation to worship according to the teachings and understanding of syafi'iyah in the province of Aceh.